2013
DOI: 10.1155/2013/924206
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Hepatocellular Carcinoma: Regulation, Function, and Clinical Implications

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and the third cause of cancer-related death. Poor understanding of the mechanisms underlying the pathogenesis of HCC makes it difficult to be diagnosed and treated at early stage. MicroRNAs (miRNAs), a class of noncoding single-stranded RNAs of ~22 nucleotides in length, posttranscriptionally regulate gene expression by base pairing with the 3′ untranslated regions (3′UTRs) of target messenger RNAs (mRNAs). Aberrant expression of miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 194 publications
(123 reference statements)
0
61
0
Order By: Relevance
“…PTEN is also implicated in HCV-associated HCC, where miR-21 overexpression was observed. 115 Importantly, this miRNA was evidenced to directly target PTEN mRNA, 116 therefore favoring telomerase activity directly and indirectly, 117 as already mentioned. Furthermore, miR-21 overexpression reduces the function of SPRY2 mRNA (another validated target of this miRNA), which was shown to up-regulate PTEN.…”
Section: Non-coding Rnas In Telomerase Regulation By Oncogenic Virusesmentioning
confidence: 59%
“…PTEN is also implicated in HCV-associated HCC, where miR-21 overexpression was observed. 115 Importantly, this miRNA was evidenced to directly target PTEN mRNA, 116 therefore favoring telomerase activity directly and indirectly, 117 as already mentioned. Furthermore, miR-21 overexpression reduces the function of SPRY2 mRNA (another validated target of this miRNA), which was shown to up-regulate PTEN.…”
Section: Non-coding Rnas In Telomerase Regulation By Oncogenic Virusesmentioning
confidence: 59%
“…Various miRNAs are oncogenic in HCC, including miR-21, miR-221, miR-222 and miR-151; however it has been suggested that a number of miRNAs, including miR-29, miR-122, miR-125b, miR-101 and miR-139, may be tumor suppressive in HCC (17). It has previously been demonstrated that in HCC, miRNAs are involved in the regulation of cell survival and proliferation, angiogenesis and metastasis (9,17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating HCC have demonstrated that miRNA expression profiles are signatures of HCC development and progression (6)(7)(8). Various miRNAs, including miR-302d, have been implicated in the onset and development of HCC (9). The identification of novel functions of specific miRNAs may help elucidate the molecular mechanisms that underlie HCC development and progression.…”
Section: Introductionmentioning
confidence: 99%
“…15e17 Recent studies have demonstrated that miRNAs are important in OC activation and development of hepatocellular carcinoma (HCC). 18,19 HCC represents 90% of primary liver cancers, it has poor prognosis, and its incidence is increasing worldwide. 20 A study from Gailhouste et al 21 identified direct targeting of DNA methyltransferase 1 by the hepatospecific miR-148a (down-regulated in HCC patients, mouse, and human HCC cell lines) to be critical for hepatic differentiation.…”
mentioning
confidence: 99%
“…miRNA expression is dysregulated in various types of cancer, including HCC. 19,22,23 The miR-133 family (miR-133a-1, miR-133a-2, and miR133b) is among the most studied miRNAs. 24 These miRNAs are transcribed as bicistronic RNAs together with miR-1-2, miR-1-1, and miR-206, respectively.…”
mentioning
confidence: 99%